Laparoscopic and Laparotomic Restaging in Patients With Apparent Stage I Epithelial Ovarian Cancer: A Comparison of Surgical and Oncological Outcomes - Wang, Yongxue; Yin, Jie; Li, Yan; Shan, Ying; Gu, Yu; Jin, Ying (Frontiers in Oncology, 2022)
Objective: To assess the surgical and oncological outcomes of laparoscopic restaging compared with laparotomy for apparent early-stage epithelial ovarian cancer. Methods: A retrospective chart review was undertaken of patients who underwent laparoscopic (laparoscopy group) or laparotomic (laparotomy group) restaging at the Peking Union Medical College Hospital, China, between January 2012 and December 2017. All patients had apparent stage I epithelial ovarian cancer that was incompletely staged at the initial surgery. Results: A total of 157 patients were included, with 50 in the laparoscopy group and 107 in the laparotomy group. Baseline characteristics were similar between the groups. No cases were converted from laparoscopy to laparotomy. The laparoscopy group had a significantly shorter operating time (p<0.001), less estimated blood loss (p<0.001), and a shorter postoperative hospitalization duration (p<0.001) than the laparotomy group. Transfusions were required in only eight laparotomy patients. No significant differences in postoperative complications were observed between the two groups (p=0.55). Eighteen (11.5%) patients were upstaged to stage II or stage III after surgery. A total of 123 (78.3%) patients received postoperative platinum-based chemotherapy. During the follow-up period, 15 (9.6%) patients experienced disease recurrence, and 3 patients died of disease progression. Five-year disease-free survival (p = 0.242, log-rank test) and overall survival (p = 0.236, log-rank test) were not affected by the surgical approach. Conclusions: Laparoscopic restaging showed more favorable operative outcomes than laparotomy. Surgical restaging via laparoscopy versus laparotomy was not associated with worse survival in women with apparent stage I epithelial ovarian cancer.